THE DEVELOPMENT OF MULTIMEDIA-ASSISTED LANGUAGE LEARNING TO IMPROVE ENGLISH SKILL OF ELEMENTARY SCHOOL STUDENTS - Hesti Kusumaningrum; Zulfiati Syahrial (International Journal of Education, Information Technology, and Others, 2018)
The purpose of this study is to analyze (1) the phases of developing a Multimedia Assisted Language Learning (MALL) for Elementary school students, (2)the attractiveness of the MALL, and (3)the effectiveness by analyzing the student’s achievement. Formative evaluation is done to measure the quality of MALL. This product was evaluated by 1 subject matter expert and 1 media specialist. The subjects of the research trial included 91 students, consisted of 34 students for the research instruments trial, 7 students for the small group trial, and 50 students for the field trial. Data were collected using questionnaires and tests (pre-test and post-test). The data were in the form of recommendation for the product improvement, Likert-scale analysis, and test scores. The result of this research and development shows that the attractiveness of the developed multimedia, observed from: (1)the product appearance aspect is in a good category, with the average score of 4.00, (2)the learning material aspect is in a good category, with the average score of 4.02, (3)the motivation of learning using the multimedia is in a very good category, with the average score of 4.09. The average score improvement of the pre-test score to the post-test is around 20 or equal to 35%. The t-test result indicates that there is a significant improvement of student’s average scores from the pre-test to the post-test, with p < 0.05, we can conclude that the developed MALL are effective for Elementary School students.